DAYA TERIMA COOKIES DAUN KELOR (MORINGA OLEIFERA) SEBAGAI ASI BOOSTER UNTUK IBU MENYUSUI - Yossy Anggraeni; Imelda Telisa; Sartono Sartono; Yuli Hartati; Yunita Nazarena (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2026)
Background: Breast milk is the primary source of nutrition for infants, but many breastfeeding mothers face challenges related to both the quantity and quality of their breast milk. Consuming functional foods such as moringa leaves, which contain lactagogue compounds, offers a natural alternative to support milk production. Cookies are chosen as a practical food product because they are easy to consume and can be combined with moringa leaves to help meet the nutritional needs of breastfeeding mothers. Objective: To determine the acceptability of moringa leaf cookies (Moringa oleifera) as a breast milk booster for breastfeeding mothers and to analyze the nutritional content of the best formulation. Methods: This research used an experimental method with a completely randomized design (CRD) consisting of three treatments: F1, F2, and F3. A total of 30 untrained panelists conducted organoleptic evaluations based on color, aroma, taste, texture, and aftertaste. Nutritional analysis of the best formulation was performed through proximate tests and iron content measurement. Results: The F2 formulation (with the addition of 10 grams of moringa leaf powder) showed the highest acceptability across all organoleptic attributes. Laboratory analysis of F2 cookies revealed the following nutritional content per 100 grams: 526.91 kcal energy, 7.58 g protein, 29.59 g fat, 57.57 g carbohydrates, and 4.36 mg iron. Conclusion: The F2 moringa leaf cookie formulation had the best acceptability and has the potential to serve as a functional snack that supports the nutritional needs of breastfeeding mothers.